A near-infrared intelligent molecular rotor with aggregation induced-emission for viscosity detection of liquids. Issue 8 (15th March 2022) - Xu, Lingfeng; Huang, Yanrong; Peng, Xinkang; Wu, Kui; Huang, Chunfang; Liu, Limin
Abstract : A near-infrared AIE-based intelligent molecular rotor was designed for viscosity detection during the beverage spoilage process. Abstract : Liquid safety has become a widespread issue, due to the potential adverse effects on public health. To the best of our knowledge, viscosity might be a representative physical parameter during the food deterioration process. Monitoring viscosity variation during the food spoilage process is of great importance, thus a convenient inspection technique with rapid detection, high sensitivity, a simple detection process, and fast results output needs to be found. Herein, a near-infrared intelligent molecular rotor (DPADQ) is proposed to describe the micro-viscosity via a fluorescence analytical method with a typical turn-on fluorescence signal. This molecular rotor has a flexible donor–π–acceptor conjugated structure and forms a typical twisted intramolecular charge transfer system. DPADQ features a large Stokes shift (203 nm in the highly viscous glycerol system), longer wavelength emission (725 nm) and typical aggregation-induced emission character. Due to its excellent optical properties, especially the viscosity-sensitive coefficient of 0.55, a thickening effect with various food gums was determined. And the capability of DPADQ to evaluate the spoilage extent of beverages with viscosity variations as a robust indicator was explored as well. The results indicated that a linear relationship can be found between the viscosity variations and fluorescence fluctuations. This strategy can motivate us to design multi-functional molecular tools for food safety inspection with the use of the fluorescence analytical technique.